2013
DOI: 10.1155/2013/715843
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Measurement of Living Cells in Methanol with Digital Holographic Microscopy

Abstract: Cell morphology is the research foundation in many applications related to the estimation of cell status, drug response, and toxicity screening. In biomedical field, the quantitative phase detection is an inevitable trend for living cells. In this paper, the morphological change of HeLa cells treated with methanol of different concentrations is detected using digital holographic microscopy. The compact image-plane digital holographic system is designed based on fiber elements. The quantitative phase image of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Cell volume changes, resulting from cytotoxic treatments or apoptosis events, have recently been investigated with DH microscopy [11,[21][22][23][24][25]. When cells go in to early apoptosis, the first discernible indication is an increase in the cell phase shift followed by a decrease as the cell eventually dies [21].…”
Section: Cell Death Of Adherent Cellsmentioning
confidence: 99%
“…Cell volume changes, resulting from cytotoxic treatments or apoptosis events, have recently been investigated with DH microscopy [11,[21][22][23][24][25]. When cells go in to early apoptosis, the first discernible indication is an increase in the cell phase shift followed by a decrease as the cell eventually dies [21].…”
Section: Cell Death Of Adherent Cellsmentioning
confidence: 99%
“…Recently, it has been demonstrated that DHM provides quantitative monitoring of physiological processes through structural analysis and functional imaging which, for example, gives new insight into signaling of cellular water permeability [19], [20], cell morphology changes due to toxins [21][24] and infections [25][27] as well as micro-calcification, cancer and inflammation mediated tissue alterations [12], [28] and bacteria and mammalian single cell growth [29][32].…”
Section: Introductionmentioning
confidence: 99%
“…Digital holographic microscopy (DHM), a variant of quantitative phase microscopy, enables not only stain-free quantitative phase contrast imaging but also assessment of cell thickness and tissue density by measuring optical path length delay [16] [18] . Recently, it has been demonstrated that DHM provides quantitative monitoring of physiological processes through structural analysis and functional imaging which, for example, gives new insight into signaling of cellular water permeability [19] , [20] , cell morphology changes due to toxins [21] [24] and infections [25] [27] as well as micro-calcification, cancer and inflammation mediated tissue alterations [12] , [28] and bacteria and mammalian single cell growth [29] [32] .…”
Section: Introductionmentioning
confidence: 99%
“…DH has growing applications in biological cell imaging, microstructure detection, particle field analysis, and temperature field measurement etc. [1][2][3][4][5][6]. The resolution of a digital holographic system is directly related to the numerical aperture (NA) of the recording device and the wavelength used in the recording.…”
Section: Introductionmentioning
confidence: 99%